METHODS OF TEACHING SCIENCE “EDUCATION” IN THE CONDITIONS OF MULTIFACETED DEVELOPMENT OF THE COUNTRY - Mengdobilova M. Q. (European Science Publishing, 2024)
In this article, the process of globalization and popular culture on the world scale, the negative impact of the process of globalization on youth education, nationalism, the result of reforms in the system of teaching social and humanitarian sciences in our country, including the teaching of the subject "Education" in general education schools in the education of a competent generation, as well as in the formation of ideological immunity significance was analyzed.
Keywords: globalization process, mass culture, ideological threats, Western individualism, egocentrism, nihilism, indifference, cynicism, violence, manqurt, moral disarmament, national values, national education, enlightenment.